Academic Discussion On Kurikulum Merdeka Focusing On Primary Teachers At Barito Kuala Indonesia - Angga Taufan Dayu; Yudha Aprizani; N Islamiah (OMNICODE Journal (Omnicompetence Community Developement Journal), 2022)
The goal of this community service is to educate teachers at SDN 2 Alalak Batola on the new paradigm curriculum. This community service program lasted three days and also was attended by all of the teachers. The main activity begins with an introduction to the new paradigm curriculum, including understanding, stages, benefits, and drawbacks, and is followed by concrete examples of learning approaches based on previous research findings. The outcomes of this service show that teachers' understanding and skills are improving, allowing them to support learning in the classroom.